Chemical properties of the soil fertilized with potassium and calcium in guava cultivation cv. 'Paluma' - Cavalcante, Alian Cássio Pereira; Cavalcante, Lourival Ferreira; Cavalcante, Adailza Guilherme [UNESP]; Bertino, Antonio Michael Pereira [UNESP]; Bertino, Antonio Missiemario Pereira; Ferreira, Nubia Marisa (Southern Cross Publishing, 2018)
Soil fertility gradually declines over time and under continuous cultivation. It negatively reflects on the yield and quality of crop production, including guava, which is a perennial fruit of high economic potential. Therefore, the objective of this study is to evaluate the effect of potassium doses with and without the application of calcium in soil cultivated with guava Paluma. The experimental design was a randomized block with factorial arrangement of 2 × 5, relative to the soil with and without 120 g plant -1 year -1 calcium (using calcium nitrate) and five doses of K 2 O from 0, 45, 90, 135, and 180 g plant -1 year -1 in the form of potassium chloride. The variables analyzed in soil were potential hydrogen, organic matter, phosphorus, potassium, calcium, magnesium, sodium, sum of bases, hydrogen plus aluminum, aluminum, cation exchange capacity, and soil base saturation. The soil fertility was higher in the treatments with potassium (K) fertilizer which has recommended doses between 90 and 135 g plant -1 year -1 without application of calcium in the soil.
Keywords: Fertilization; Frit; Psidium guajava; Soil; Soil fertility